3x + 5y = -1 2x - 5y = 16 Add the two equations: 5x = 15 or x = 3 Substitute for x in the first equation: 3*3 + 5y = -1 15 + 5y = -1 5y = -10 so y = -10/5 = -2 The solution is (x, y) = (3, -2)
Because of the limitations of the question software, it was not possible to determine what the original equation was supposed to be, so we assumed it is 3x + 5y = 7. It could have just as easily been 3x - 5y = 7, or even 3x/5y = 7.So, let's solve them all for x.3x + 5y = 73x = 7 - 5yx = (7 - 5y)/3How about 3x - 5y = 7?3x - 5y = 73x = 7 + 5yx = (7 + 5y)/3And 3x/5y = 7?3x/5y = 73x = 35yx = 35y/3 Solving for y The above equations wrote the equation so that x is a function of y, not the other way around. Here's how to rewrite the equation so that y is a function of x: 3x + 5y = 7 5y = -3x + 7 y = (-3x + 7)/5
Multiply the first equation by 3 to give 9x + 15y = 21
To solve this, present the equation in the standard slope/intercept form of y = mx + c. 'm' is the slope. 2x + 5y = 10 5y = -2x + 10 y = -2/5x + 2 Therefore, -2/5 is the slope.
Solving for y: 5y = 9 + 2y 5y - 2y = 9 3y = 9 y = 9/3 = 3
40 + 9 = 5y + 9 Since 9 is present on both sides of the equation,therefore we can strike it off on both sides,the remaining equation being 40 = 5y or 5y = 40 5y = 40 or y = 40/5 Therefore,y = 9 .
Oh, dude, you just gotta rearrange that equation a bit. So, like, first divide by 5 to get -4x - y = 8. Then, if you wanna be all fancy and use slope-intercept form, just solve for y to get y = -4x + 8. And there you have it, a technically correct answer with a sprinkle of my signature humor.
First, you must simplify the equation.(-5y)=(-300)[Divide by -5]y=60Now, the equation is as simple as it can be. Draw a horizontal line across y's 60. You are now finished!
It's a non-standard form of the equation for a straight-line graph with a slope of 18 and a y-intercept of 16.
In order to graph this equation, you have to isolate y. 3x + 5y = -2 3x + 5y + 2 = 0 3x + 2 = -5y (3x+2)/-5 = y Now you can plug it into a graphing calculator. If you're graphing by hand, the equation you'll want to use is: (-3/5)x - (2/5) = y So the slope will be negative 3/5 and the y-intercept is -2/5.
First, put the equation in slope-intervcept form y=mx + b 5y=4x + 40 The y intercept is where x=0 so- 5y= 4(0) +40 solve for y y intercept = (0,8) For the x intercept, y=0 0=4x+40 -4x=40 x= -10 xintercept =( -10.0)
4x+5y = 7 5y = -4x+7 y = -4/5x+7/5 in slope intercept form So the slope of the perpendicular line is plus 5/4
x + y = 5y = -x + 5The graph is a straight line, with [ slope = -1 ], passing through the point [ y = 5 ] on the y-axis.
6x - 5y = 36At the x-intercept, y=0.6x = 36x = 6
x + 5y = 0Subtract 5y from each side of the equation, just to put 'x' and 'y' on opposite sides.x = -5yThis is interesting. If EITHER 'x' OR 'y' is zero, then the other one is also zero.The only place on the graph where that is true is the origin. So the line goes through the origin,and the 'x' and 'y' intercepts are both zero.
To convert the equation 8x - 5y = -40 into slope-intercept form (y = mx + b), where m is the slope and b is the y-intercept, you need to solve for y. First, isolate y by subtracting 8x from both sides to get -5y = -8x - 40. Then, divide by -5 to get y = 8/5x + 8, which is the slope-intercept form of the equation. The slope is 8/5 and the y-intercept is 8.
-4x + 5y = 10Add 4x to each side:5y = 4x + 10Divide each side by 5:y = 0.8x + 2The graph of this equation is a straight line with [ slope = 0.8 ] and [ y-intercept = 2 ].